The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.solmat.2019.110264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soiling and weathering on the albedo of building envelope materials: Lessons learned from natural exposure in two European cities and tuning of a laboratory simulation practice

Abstract: • We selected sixteen roofing and four wall finish products • We naturally aged them for four years in Rome and Milan and exposed them in the lab • The mean absolute albedo difference (natural-lab) of roofing products is 0.027 • ASTM D7897 can be adapted to mimic weathering and soiling out of the U.S.A. • We identified possible improvements to natural aging and lab exposure practices

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 40 publications
(94 reference statements)
0
12
0
4
Order By: Relevance
“…As such, [71] found that increasing the albedo of all roofs in Sydney can reduce the UHI by 0.6 • C, while [80] reported that an increase in the albedo of 60% of Melbourne's rooftops can lead to a cooling potential of 0.5 • C. Furthermore, the thermal performance of a cool roof depends on many factors, such as local climatic conditions (solar radiation intensity, humidity, wind speed, and cloud cover), the solar reflectance and thermal emittance of roof materials, heat capacity, and U-value of the roof [65]. Moreover, ageing can remarkably reduce the solar reflectance-and thus the cool roof direct and indirect benefits-even by more than 20% during the first years for cool roofing materials with initial albedo equal to 80%, as documented with natural exposure programs conducted in the US, Europe, Brazil, and Japan [112].…”
Section: Cool Roofs and Façadesmentioning
confidence: 80%
“…As such, [71] found that increasing the albedo of all roofs in Sydney can reduce the UHI by 0.6 • C, while [80] reported that an increase in the albedo of 60% of Melbourne's rooftops can lead to a cooling potential of 0.5 • C. Furthermore, the thermal performance of a cool roof depends on many factors, such as local climatic conditions (solar radiation intensity, humidity, wind speed, and cloud cover), the solar reflectance and thermal emittance of roof materials, heat capacity, and U-value of the roof [65]. Moreover, ageing can remarkably reduce the solar reflectance-and thus the cool roof direct and indirect benefits-even by more than 20% during the first years for cool roofing materials with initial albedo equal to 80%, as documented with natural exposure programs conducted in the US, Europe, Brazil, and Japan [112].…”
Section: Cool Roofs and Façadesmentioning
confidence: 80%
“…A roof with high thermal mass but a dark surface may behave similar to a roof with a relatively low mass and thermal inertia but with a highly reflective surface. A highly reflective surface would almost nullify the effects of the solar cycle; nevertheless, it would be difficult to preserve due to soiling or biofouling, hence the lower solar reflectance of the aged surface must be considered [31,32]. Moreover, highly reflective surfaces are white, but different, less reflective colors may be compulsory for historical or traditional buildings or even entire urban areas.…”
Section: The Solar Transmittance Factor (Stf) and The Solar Transmittance Index (Sti)mentioning
confidence: 99%
“…La existencia de una amplia gama de productos y tecnologías de estabilización química de suelos, hace necesario que se realice una selección adecuada mediante la evaluación de su durabilidad, propiedad que está relacionada con la resistencia al intemperismo, a la erosión o a la abrasión del tránsito de aquellos suelos cercanos presentes en la superficie de rodadura (Camacho Tauta et al, 2008). Los suelos, y en general todos los materiales expuestos a la intemperie, pueden sufrir deterioros por condiciones ambientales como la lluvia, la radiación UV, el rocío, la humedad; de allí la importancia de poder conocer la incidencia de estos factores, individuales y combinados, sobre sus propiedades (Paolini et al, 2020). Es así como resulta de gran interés el uso de Studies in Engineering and Exact Sciences, Curitiba, v.3, n.1, p.2-15, jan./mar.…”
Section: Introductionunclassified